Decisive impact of social media on GE13 - Singh, Habhajan (Malaysian Reserve, 2013)

(untitled)
"IT'S tough," said one Ipoh-based Umno leader. "We have an intense fight on our hands, the toughest perhaps." The Barisan Nasional (BN) stalwart was talking about the ongoing campaigning for the 2013 General Election (GE13).